2019
DOI: 10.1210/clinem/dgz150
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Primary Aldosteronism by Seated Saline Suppression Test—Variability Between Immunoassay and HPLC-MS/MS

Abstract: Background In primary aldosteronism (PA), excessive, autonomous secretion of aldosterone is not suppressed by salt loading or fludrocortisone. For seated saline suppression testing (SSST), the recommended diagnostic cutoff 4-hour plasma aldosterone concentration (PAC) measured by high-performance liquid chromatography–mass spectrometry (HPLC-MS/MS is 162 pmol/L. Most diagnostic laboratories, however, use immunoassays to measure PAC. The cutoff for SSST using immunoassay is not known. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Previous studies reported significant variations between different IAs ( 12 , 14 , 16 ). In our study, IA measurement was on average 31 ng/L higher than LC-MS/MS quantification, and this is well in line with previous reports despite good correlation ( 28 , 42 , 43 ). Even by using highly sensitive and specific IAs like in this study, the lower limit of quantification is significantly higher in IA compared to LC-MS/MS.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported significant variations between different IAs ( 12 , 14 , 16 ). In our study, IA measurement was on average 31 ng/L higher than LC-MS/MS quantification, and this is well in line with previous reports despite good correlation ( 28 , 42 , 43 ). Even by using highly sensitive and specific IAs like in this study, the lower limit of quantification is significantly higher in IA compared to LC-MS/MS.…”
Section: Discussionsupporting
confidence: 93%
“…The study population included all members of LHS who were tested for COVID-19 infection during the study period and who had at least one previous test for plasma 25 (24). According to LHS guidelines, blood was collected from fasting persons and transported on ice to the Center Laboratory for processing within 4 h of collection using DiaSorin Chemiluminescence assay (25)(26)(27)(28). Data of each subject were collected from the LHS computerized database and included age, gender, socioeconomic status (SES), weight, height, body mass index, current smoking status, psychiatric and somatic comorbidities, and hospitalizations as a result of the COVID-19 infection.…”
Section: Methodsmentioning
confidence: 99%
“…The saline infusion test is widely used for confirming the diagnosis of primary aldosteronism but has important limitations [34]. Recently, a seated version of the test has been established providing comparable testing conditions to our study [35]. Remarkably, exenatide seems to be at least as potent as saline loading to suppress aldosterone in healthy volunteers [35].…”
Section: Discussionmentioning
confidence: 70%
“…Recently, a seated version of the test has been established providing comparable testing conditions to our study [35]. Remarkably, exenatide seems to be at least as potent as saline loading to suppress aldosterone in healthy volunteers [35]. Further studies are warranted to directly explore the potential of GLP1 RAs in the diagnostic workup of hyperaldosteronism.…”
Section: Discussionmentioning
confidence: 88%